ASSESSING THE IMPACT OF VERTEBRATE PEST-INDUCED ON-FARM MAIZE LOSSES ON YIELDS, INCOME, FOOD SECURITY AND FARMERS’ LIVELIHOOD IN IFELODUN LOCAL GOVERNMENT AREA, KWARA STATE, NIGERIA - Aboyeji, Olurotimi Joseph (Malaysian Journal of Tropical Geography (MJTG), 2024)
In developing countries, pests’ damage to fields and stored crops substantially contributes to losses in farm yields and income. Studies have investigated the impact of insect pests on maize production, with inadequate attention on the impact of on-farm losses of maize from vertebrates. Consequently, this study examined types, stages, intensity, effects, and control of vertebrate pest-induced on-farm losses of maize as well as assess its effects on maize’s yields and income and its impact on food security and farmers’ livelihood in Ifelodun LGA, Kwara State, Nigeria. 500 Maize farmers were selected through convenient sampling from 14 randomly selected settlements in the study area. Responses were analyzed using descriptive statistics (percentages), while inferential statistics (ANOVA) was used to assess the degree of spatial variations and hypothesis testing; because of its suitability for analysis of differences among the means of more than two groups. The result shows that the majority; identified grass cutter as the vertebrate pest largely responsible for on-farm losses (38.6%), sustained on-farm losses at the fruiting stage (60.0%), described the intensity of on-farm losses as very high (58.4%), affirmed negative impact of on-farm losses from vertebrate pests on Maize’s yield and income (70.8%) and upheld the negative impact of On-farm losses of Maize from vertebrate pest on food security and farmers’ livelihood (75.4%). The result shows no significant variations in the perception of respondents on the negative impact of vertebrate pest-induced on-farm losses of maize on food security and farmers’ livelihood across the settlements (F (3,483) =0.755, P> 0.05). The study concluded and consequently recommended improvement in the control mechanisms of vertebrate pests to reduce on-farm losses to increase maize yields and income as well as improve farmer’s livelihood and food security.